Implementation of the Boek Khaman Creative House from CSR PT Pertamina EP Limau Field - Wilujeng, Catherine Wahyuning; Para Buana , Abdul Rachman; Sanjaya, Rama; Aznury , Martha; G. Rayes , Renato (Pelopor Publikasi Akademika, 2025)
Batik is one of the cultural heritage of the Indonesian nation that has been known and developed since ancient times. As part of the craft arts, batik not only functions as a textile product, but also represents the aesthetic value, philosophy, and cultural identity of the community. This research is in the form of a qualitative field study or field research to study the program. The results of the research show that the Boek Khaman Creative House is a community empowerment initiative initiated by the Lubuk Raman Village Youth Organization with the support of PT Pertamina EP Limau Field and various stakeholders. This program is here as an effort to overcome the problem of low group solidity, limited market access, and lack of continuity of creative economy activities at the village level. Through a collaborative approach, this program focuses on developing the potential of human resources and utilizing local natural resources to create productive economic activities, especially through typical batik innovations known as Khaman Batik. The results of measuring the impact of the program implementation, PT Pertamina EP Limau Field uses several approaches that include the dimensions of nature, economy, society, and wellbeing, showing that this program is beneficial to the community.